THE SPATIAL PLANNING OF SUSTAINABLE TRANSPORTATION: STUDY CASE OF SEMARANG CITY - Nihayah, Dyah Maya; Nurfitrokha, Yunilia (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2019)
As capital of Central Java, Semarang City has high accessibility since it has harbor, airport, and as the main lane of the mobility. The common urban issues felt by the community are traffic, air pollution, and the lack of public facilities for the non-motorize such as pedestrian track. It is necessary for urban managers and planners to conduct necessary planning and analysis for the development of urban transportation system through a strategic perspective. The objective of this article is to determine the process of spatial planning prioritized to achieve a sustainable transportation in Semarang City. This research was qualitative descriptive. Data were analyzed using the Analysis Hierarchy Process Method. The result showed that the planning of sustainable spatial transportation in Semarang City was arranged by some criteria in its planning; economic aspect, environment and the third is social aspect. The planning of sustainable transportation can be done by providing mode of reliable and well integrated mass transportation, the determining of policy of one RTH for one sub-district and providing a City Walk (a free vehicle area) so that the a friendly non-motorize city concept could be created